Pack Aluminizing of Zirconium 702 Alloy to Improve Surface Hardness and Wear Resistance - Muhaffel, Faiz (Manufacturing Technologies and Applications, 2025)
Zirconium 702 (Zr 702) alloy exhibits excellent corrosion resistance but suffers from low hardness and poor wear resistance, limiting its use in wear-intensive applications. In this study, a pack aluminizing treatment was applied to Zr 702 to form a hard aluminide surface layer aimed at improving its tribological performance. Characterization by X-ray diffraction (XRD) and cross-sectional scanning electron microscopy/energy-dispersive spectroscopy (SEM/EDS) confirmed the formation of a continuous diffusion coating approximately 40 µm thick, composed predominantly of an Al-rich intermetallic phase (mainly Al3Zr). This aluminized layer was dense, well-adhered, and significantly harder than the substrate, with a Vickers microhardness of 703.1 ± 76.7 HV0.025 compared to 182.9 ± 20.7 HV0.025 for untreated Zr 702. In dry sliding reciprocating wear tests (2–4 N loads against an alumina counterface), the aluminized sample exhibited a much lower and more stable coefficient of friction (COF), reaching a steady value of about 0.35 under 4 N load, whereas the untreated Zr 702 stabilized around 0.6 under the same conditions. In comparison with the untreated Zr 702, the aluminized surface exhibited about a 70% reduction in wear volume under a 4 N load as a result of the improved hardness and modification of its surface with an intermetallic layer. Wear track analysis further revealed that the dominant wear mechanism shifted from severe adhesive and abrasive wear in the untreated Zr 702 to a mild abrasive/oxidative wear mode in the aluminized sample, as the hard intermetallic layer protected the underlying Zr from significant damage. Overall, the pack aluminizing process remarkably enhanced the surface hardness, frictional behavior, and wear resistance of Zr 702, demonstrating an effective surface engineering approach to improve the tribological performance of zirconium alloys.